METHOD OF SELECTING THE PARAMETERS OF DIAGNOSTIC ELEMENTS OF VEHICLES OF URBAN ELECTRIC TRANSPORT - Шавкун, Вячеслав; Окрутний, Андрій; Мухін, Микола (SWorldJournal, 2023)
The work considers the methodology of developing algorithms and calculation programs, optimal periodicity of diagnosing structural units of the object of diagnosis. It is proved that the decision regarding effective exploitation should always be made on t